(untitled) (Fiep Bulletin - online, 2014)
Evaluation of pupils in the class of physical education can be objective if it is a product of following three basic elements:educational component, pedagogical component and the condition of the motor capabilities of the pupil. The goal of our research wasthe third component of the evaluation, in other words, to measure the motor capabilities of the pupils and to construct a universal table ofevaluation for pupils of this age in R. Macedonia.The sample for this research of transversal character was consisted out of 193 male pupils at age of 10 years old that regularlyvisited classes of physical education in 8 primary schools in R. Macedonia. The pupils were tested on 8 motor tests, the realization of whichis very simple because the tests don’t need special or expensive tools to be carried out and lot of class teachers will be able to performthem. After processing the statistical data of the gained results, the obtained frequencies of the distributions as well as the results from the calculated percentiles helped as a base for establishing the normative tables for the pupils.